Analisis Pengaruh Kepuasan Wajib Pajak Dan Kepercayaan Kepada Pemerintah Daerah Terhadap Kepatuhan Pajak Bumi Dan Bangunan Pada Badan Pengelolaan Pendapatan Asli Daerah Kabupaten Bogor - Syachmitha Dewi Putri Wahyudi; Mahwiyah Mahwiyah; Siti Asmonah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to: a) determine the effect of taxpayer satisfaction on compliance in paying Land and Building Tax (PBB) at the Bogor Regency Regional Original Revenue Management Agency, b) determine the effect of trust in the local government on compliance in paying PBB at the Bogor Regency Regional Original Revenue Management Agency, and c) determine the effect of taxpayer satisfaction and trust in the local government simultaneously on compliance in paying PBB at the Bogor Regency Regional Original Revenue Management Agency. The method used is a quantitative approach. Data collection was conducted through a questionnaire using a purposive sampling technique. The results show that taxpayer satisfaction has no effect on compliance in paying PBB at the Bogor Regency Regional Original Revenue Management Agency, trust in the local government has an effect on compliance in paying PBB at the Bogor Regency Regional Original Revenue Management Agency; and taxpayer satisfaction and trust in the local government have a significant effect on compliance in paying PBB at the Bogor Regency Regional Original Revenue Management Agency.